Strategi Komunikasi Pemerintah Kota Tangerang Untuk Memberikan Informasi Kepada Masyarakat Melalui Aplikasi Tangerang Live - Nurmiftah Fauzi; Titi Stiawati; Ipah Ema Jumiati (Publikasi Indonesia, 2023)
This study aims to determine the communication strategy of the Tangerang City Government to provide information to the public through the Tangerang Live application. The object of this research is a communication strategy to the public through the Tangerang Live application. This research uses secondary data sources or literature searches. The results of this study indicate that the Tangerang City Government has issued an application called Tangerang LIVE, as a means of communication for the Tangerang City Government and the community. This is because today's technology has become a human need to find information that can be obtained in minutes or even seconds. With the strong and rapid development of technology, government organizations change the behavior of both written and oral communication. The Tangerang LIVE application contains various application features such as Electronic News, LAKSA, Emergency 112, Ready for Work, SEGAR, Sympathy Hospital, Online Licensing. In addition, the socialization of the Tangerang Live application through the abbreviation flattering which means Visiting Tuesday, exhibitions and forums created with the participation of residents of the city of Tangerang which are held in the Village and District.